SCENARIO PLANNING FOR IMPROVING COMPANY PERFORMANCE THROUGH OPTIMIZATION OF INNOVATIVE MANAGEMENT: A CASE STUDY AT PUPUK INDONESIA GROUP - Sischa Maulana; Syamsul Ma’arif; Arry Ekananta (RADJA PUBLIKA, 2026)
This study concludes that, in general, the Work Motivation, Work Engagement, and Learning Agility of innovators at PT Pupuk Indonesia (Persero) and its subsidiaries are in the very good category. Innovators demonstrate strong motivation in maintaining operational efficiency, high levels of work engagement with the company, and solid learning capabilities derived from data and technical experience. Nevertheless, several challenges remain, including operational complexity, fluctuations in work energy due to daily workloads, and the need to strengthen capabilities in dealing with unstructured and strategic changes. The results of statistical testing indicate that Work Motivation, Work Engagement, and Learning Agility have a significant effect on Innovator Work Productivity. This study also finds that Innovator Work Productivity has a significant effect on Corporate Performance, indicating that innovator productivity plays an important role in driving overall corporate performance. Furthermore, Innovator Work Productivity is proven to mediate the influence of Work Motivation, Work Engagement, and Learning Agility on Corporate Performance, underscoring the strategic role of innovators as key drivers of corporate performance. In anticipation of future dynamic changes, this study has developed four scenario planning alternatives that can be utilized by the company to address potential changes in innovator productivity and corporate performance conditions. The study also provides recommendations for company management to optimize the innovator management function within the organization.